PFAS destruction using supercritical water oxidation (SCWO) at Peterson Space Force Base - Hallie Webb; Stephen Rosansky; Samer Mohamad Al-Dirani; Kavitha Dasu; Christopher G. Scheitlin; Jeff Davis; Leonardo Chiques (Journal of Hazardous Materials Letters, 2025)
Per- and polyfluoroalkyl substances (PFAS) have become a top environmental concern for the military due to the prevalence of PFAS contamination from aqueous film-forming-foams (AFFFs) used to suppress fires in emergencies and training exercises. Supercritical water oxidation (SCWO) has emerged as a promising technology for the removal and destruction of PFAS in aqueous media. This project used the SCWO-based PFAS Annihilator® at Peterson Space Force Base to treat unconcentrated, 50 %, and 79 % concentrated PFAS-contaminated water onsite and demonstrate the efficacy of the technology. This study analyzed target PFAS, total organofluorine, and non-PFAS contaminants removed by the SCWO system. Here, 94.3 % of target PFAS in the unconcentrated influent, 99.2 % in the 50 % concentrated influent, and 99.7 % in the 79 % concentrated influent were destroyed, while removing > 95.5 % of total organofluorine, with limited byproducts in the aqueous and vapor effluent. The mass balance achieved 52–102 % fluoride recovery across the three concentrations. A novel cost assessment demonstrates improved economic efficiency with increasing influent concentration, suggesting that SCWO can efficiently remove and destroy PFAS from contaminated water to levels below regulatory requirements, solidifying itself as an innovative solution to PFAS contamination.